A phase separation method for analyses of fluoroquinones in meats based on ultrasound-assisted salt-induced liquid–liquid microextraction and a new integrated device. (August 2015) - Wang, Huili; Gao, Ming; Xu, Youqu; Wang, Wenwei; Zheng, Lian; Dahlgren, Randy A.; Wang, Xuedong
Abstract: Herein, we developed a novel integrated device to perform phase separation based on ultrasound-assisted, salt-induced, liquid–liquid microextraction for determination of five fluoroquinones in meats by HPLC analysis. The novel integrated device consisted of three simple HDPE (high density polyethylene) parts that were used to separate the solvent from the aqueous solution prior to retrieving the extractant. The extraction parameters were optimized using the response surface method based on central composite design: 589 μL of acetone solvent, pH 2.1, 4.1 min extraction time and 3.5 g of Na2 SO4 . The limits of detection were 0.056–0.64 μg kg − 1 and recoveries were 87.2–110.6% for the five fluoroquinones in muscle tissue from fish, chicken, pork and beef. This method is easily constructed from inexpensive materials, extraction efficiency is high, and the approach is compatible with HPLC analysis. Thus, it has excellent prospects for sample pre-treatment and analysis of fluoroquinones in meat samples. Highlights: An integrated apparatus was developed using three simple high-density polyethylene components. The apparatus quickly separates the extractant from the aqueous phase prior to retrieving. The novel device can be easily integrated with the PS-MSLM method. The LODs of this method are low (0.056–0.64 μg kg − 1 ) for meats. The extraction time of this method is short (ca. 13.1 min).